2010
DOI: 10.5251/abjna.2010.1.4.430.439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farmyard manure and inorganic fertilizers on maize production on Alfisols and Ultisols in Kakamega, western Kenya

Abstract: Soil acidity is one property associated with decline of most crop productivity. Alfisols and Ultisols are some of the acidic soils predominant in western Kenya. An experiment was conducted in both soils to find out the effect of farmyard manure (FYM) and inorganic fertilizers on maize yield on farmers' fields during wet and dry seasons of 2006. The experiment, laid out in a randomized complete block design (RCBD), had five replications in each soil type. The treatments were: farmer's practice, N (60 kg ha ). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 8 publications
5
36
2
1
Order By: Relevance
“…In CN, the low pH values of both layers studied may also be related to the intensive use of nitrogen fertilizers, mainly as ammonium or amide, which generate H + to be nitrified in the soil (ACHIENG et al 2010;YANG et al, 2012), favoring soil acidity. The areas in environmental recovery and with remnants of native vegetation had significantly higher pH values due to addition of plant residues and transformation processes of OM by intense microbial activity, which can provide higher carbon accumulation in the soil surface (EFFGEN et al, 2012).…”
Section: Results End Discussionmentioning
confidence: 99%
“…In CN, the low pH values of both layers studied may also be related to the intensive use of nitrogen fertilizers, mainly as ammonium or amide, which generate H + to be nitrified in the soil (ACHIENG et al 2010;YANG et al, 2012), favoring soil acidity. The areas in environmental recovery and with remnants of native vegetation had significantly higher pH values due to addition of plant residues and transformation processes of OM by intense microbial activity, which can provide higher carbon accumulation in the soil surface (EFFGEN et al, 2012).…”
Section: Results End Discussionmentioning
confidence: 99%
“…Planting was done in May 2008May , 2009May , 2010 at a rate of 25 kg/ha. Enriched FYM was prepared by adding 10 kg of urea by pit method in12 m 3 pit from cattle manure and subjected to microbial fermentation for 90 days before field application (Debelle et al, 2001;Achieng et al, 2010) Urea (46-0-0) and DAP (46-18-0) were used as sources of N and P, respectively. All P fertilizer and half dose of N fertilizer as per treatment were applied as basal application at planting and the remainder N was top-dressed at 35 days after planting and FYM was applied each year for one month before the sowing date.…”
Section: Methodsmentioning
confidence: 99%
“…This result concurs with Achieng et al . (2010:436), who reported that farmyard manure from a combination of cow dung and urine provide a balanced nutrition to plants and hence enhance crop productivity. Reduction in maize yield is mainly attributed to midseason drought or prolonged dry spells (Table 5) and increasing prevalence of the crop pests.…”
Section: Resultsmentioning
confidence: 99%